2016
DOI: 10.1002/chem.201600949
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Tumor Cell Response to Chemotherapy through the Targeted Delivery of Platinum Drugs Mediated by Highly Stable, Multifunctional Carboxymethylcellulose‐Coated Magnetic Nanoparticles

Abstract: The fabrication of nanoparticles using different formulations, and which can be used for the delivery of chemotherapeutics, has recently attracted considerable attention. We describe herein an innovative approach that may ultimately allow for the selective delivery of anticancer drugs to tumor cells by using an external magnet. A conventional antitumor drug, cisplatin, has been incorporated into new carboxymethylcellulose-stabilized magnetite nanoparticles conjugated with the fluorescent marker Alexa Fluor 488… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In essence, magnetic nanoparticles are state-of-the-art technology in the field of drug delivery since they can be modified with biocompatible polymers and biopolymers (poly(ethylene glycol) (PEG), cellulose, and alginic acid), carry molecular targeting agents and/or probe molecules (fluorescent labels), and simultaneously be imaged by magnetic resonance imaging (MRI). 69…”
Section: Introductionmentioning
confidence: 99%
“…In essence, magnetic nanoparticles are state-of-the-art technology in the field of drug delivery since they can be modified with biocompatible polymers and biopolymers (poly(ethylene glycol) (PEG), cellulose, and alginic acid), carry molecular targeting agents and/or probe molecules (fluorescent labels), and simultaneously be imaged by magnetic resonance imaging (MRI). 69…”
Section: Introductionmentioning
confidence: 99%
“…This behavior could be a consequence of the total formal charge of the PDO coating which is expected to remain constant after physical and/or chemical adsorption (with substitution of bonded chlorido with phenolate ligands 58−60 ) of the neutral cisplatin complex. Cisplatin loading on magnetic nanoclusters was studied in a previous work by Brabec et al 61 They have reported a study based on highly stable colloidal carboxymethylcellulose-coated magnetite nanoparticles (cMNPs) and cisplatin. The presence of a considerable amount of terminal carboxy groups at the magnetite surface, allowed, in that system, the formation of complexes with cisplatin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Studies have shown that platinum metal nanoparticles can enhance the antitumor efficacy by regulating a variety of signal channels and activating the immune system [65][66][67]. Platinum nanoparticles have been widely used in clinical applications due to their excellent catalytic performance [68], imaging ability [69], excellent photothermal conversion ability, and radiosensitization ability [70]. Fu et al [71] performed lowmagnification (Figure 4(a)) and high-magnification SEM imaging (Figure 4(b)) and TEM imaging (Figure 4(c)) on mesoporous platinum nanoparticles.…”
Section: Platinum Nanoparticlesmentioning
confidence: 99%